Designing professional development to help teachers to implement curriculum in private schools in Dubai - MARASHDEH, SUZAN (2017)
Professional development of teachers is a very essential issue to tackle with the introduction of new innovations and advancements to the educational industry and its surrounding environment. This study has overviewed literature of research on this domain before conducting the methodology that consisted to collecting teachers’ opinions through TALIS Questionnaire, developed by OECD. Results have revealed a shortage in the professional development of teachers in Dubai.